Decreased long non-coding RNA SPRY4-IT1 contributes to ovarian cancer cell metastasis partly via affecting epithelial–mesenchymal transition - Jing Yu; Qi Han; Yulan Cui (Tumor Biology, 2017)
Long non-coding RNAs play important roles in the regulation of cellular processes including cell proliferation, differentiation, and metastasis. The dysregulation of long non-coding RNAs, such as the SPRY4-IT1 (SPRY4 intronic transcript 1), has been associated with various types of malignancies. However, the functional roles and regulatory mechanism of SPRY4-IT1 in ovarian cancer remain to be elucidated. Here, we quantified the expression level of SPRY4-IT1 in ovarian cancer patients and found its downregulation in ovarian cancer tissues compared to the adjacent normal tissues. Patients with lower SPRY4-IT1 expression were associated with a relatively poor prognosis. In consistency, the expression of SPRY4-IT1 was found to be reduced in four human ovarian cancer cell lines compared to normal ovarian epithelial cells. Next, two ovarian cancer cell lines SKOV3 and HO8910 were employed in vitro assays to investigate biological functions of SPRY4-IT1 in ovarian cancer. The cell proliferation was reduced following SPRY4-IT1 overexpression in SKOV3/HO8910 cells based on 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and colony formation assays. The SPRY4-IT1 overexpression also dramatically arrested cell cycle and promoted cell apoptosis. Both wound-healing and transwell-based assays demonstrated that cell migration and invasion were inhibited following SPRY4-IT1 overexpression. Meanwhile, overexpression of SPRY4-IT1 increased E-cadherin and decreased N-cadherin and vimentin protein levels, indicating that SPRY4-IT1 may regulate ovarian cancer cell metastasis through the inhibition of epithelial–mesenchymal transition. Taken together, our findings suggest that SPRY4-IT1 regulates various cellular processes of ovarian cancer cells and its downregulation may contribute to ovarian cancer progression and metastasis partly via affecting the epithelial–mesenchymal transition.